Dictionary of drying - Hall, Carl W. (Marcel Dekker, 1979)
This book integrates terminology from the many industries utilizing drying processes - food, agriculture, forestry, mineral, and chemical - and consolidates them into one, quick reference source. It contains more than 4000 terms with encyclopedic definitions. The book provides consistently useful information to the concsultant, manufacturer, and engineer on selection, operation, and maintenance of any drying process